Optimising node density-based structural material topology using eigenvalue of thin steel and concrete plates. (May 2015) - Lee, D. K.; Shin, S. M.
<x content-type="archive" xml:space="preserve">Abstract</x> This study aimed at optimising structural material topology in terms of node and element density by using the eigenvalue of thin steel and concrete plates. The topology optimisation condition presented in this study called to maximise the natural eigenfrequency with specific eigenmodes for a given set of boundary conditions. The numerical examples for generating steel or concrete members within the given design space verified optimal solutions depending on varied-order eigenmodes and Poisson's ratio, and resulted in new shapes and topology of thin plates for use in the building construction industry.